The possibility of finding the appropriate alternative locations for urban expansion beyond the boundaries of agricultural land in the river valleys (Case Study: Villages of Al-Furat Valley) (Damascus University Journal for engineering sciences, 2021)
The aim of this research is to find the suitable alternative locations for urban expansion beyond the boundaries of the agricultural land in the study areas, by using of Remote Sensing techniques in order to support it directly with a planning scheme for the establishment of model villages rather than the traditional urban expansion. We use multispectral image of LANDSAT-8 (30m resolution, 20 march-2018)   as a means to cover the study area, which includes Al-Maraiya, located east of the Dier Azzor city on the right bank of the Euphrates River, one of the villages as case study. The method of research is based on the method of visual interpretation through the color differentiation of the components of the image and its implications of land and environment. In addition to the use of Digital Ground Elevations Model (DEM) and GIS technology. The search result is to identify alternative appropriate location to urban expansion instead of agricultural land. It is possible to generalize the and method of research to trace the surrounding area of all villages located on both sides of the Euphrates River from the point of entry into the Syrian territory to the point of departure to find the alternative site for urban expansion outside agricultural lands.
Keywords: Visual interpretation; Digital Elevation Model; Geographic Information System; Suitable development; Urban expanding in rural zones